Object-oriented application framework documentation approaches: A survey - Jani H.M.; Peck L.S. (International Institute of Informatics and Systemics, IIIS, 2023)
One major implementation of object-oriented software engineering is object-oriented application framework development. A Framework's main objective is to promote the reuse of both design and code in the development of new applications, and thus minimizes the applications development time. Normally, a user takes approximately six to twelve months of training and learning in order to become highly productive in using a specific object-oriented application framework. This current scenario tends to discourage new users in using object-oriented application frameworks for developing new applications. This is where effective framework documentation is required. The main objective of this paper is to evaluate various aspects of currently used object-oriented application framework documenting approaches. It concludes with some preliminary results of a survey on framework documentation. Based on the survey results, a newly proposed framework documenting approach is also presented.